Screening of an FDA-Approved Library for Novel Drugs against Y. pestis - David Gur; Theodor Chitlaru; Emanuelle Mamroud; Ayelet Zauberman (MDPI AG, 2021)
Yersinia pestis is a Gram-negative pathogen that causes plague, a devastating disease that kills millions worldwide. Although plague is efficiently treatable by recommended antibiotics, the time of antibiotic therapy initiation is critical, as high mortality rates have been observed if treatment is delayed for longer than 24 h after symptom onset. To overcome the emergence of antibiotic resistant strains, we attempted a systematic screening of Food and Drug Administration (FDA)-approved drugs to identify alternative compounds which may possess antibacterial activity against Y. pestis. Here, we describe a drug-repurposing approach, which led to the identification of two antibiotic-like activities of the anticancer drugs bleomycin sulfate and streptozocin that have the potential for designing novel antiplague therapy approaches. The inhibitory characteristics of these two drugs were further addressed as well as their efficiency in affecting the growth of Y. pestis strains resistant to doxycycline and ciprofloxacin, antibiotics recommended for plague treatment.